INNOVATIVE TEACHING: BLENDING TRADITION WITH CULTURAL DIVERSITY (Konferensiyalar | Conferences, 2024)
Innovative teaching practices are essential in contemporary educational settings to ensure equitable learning opportunities for all students. This paper explores the concept of inclusive teaching by examining how traditional pedagogies can be blended with cultural diversity to create a more inclusive learning environment. Drawing on existing literature and research, the paper discusses the importance of cultural diversity in education and its impact on student learning outcomes. It then proposes a framework for inclusive teaching that integrates traditional pedagogies with cultural diversity, highlighting the benefits of such an approach for both students and educators. The paper concludes by emphasizing the need for educators to embrace cultural diversity in their teaching practices to create a more inclusive and enriching learning experience for all students.